SUING THE HOUSE OF GOD: THE CASE OF CHURCH ESTABLISHMENT IN PANGKEP REGENCY - Syamsurijal Adhan (Universitas Islam Negeri Alauddin Makassar, 2017)
Although Indonesia is in fact not a theocracy state, in certain cases the state does participate in regulating the nations’ religious life. In this fashion, it is perceptible that Indonesia also does not adopt a secular ideology. The most noticeable instance for this situation is the issue of religious harmony, which has been a serious concern of the state since early on. In this case the Ministry of Religious Affairs is entrusted with responsibilities. Therefore, in the Regulation of the Minister of Religious Affairs of the Republic of Indonesia in 2010 concerning the Strategic Plan of the Ministry of Religious Affairs (MORA) for years 2010-2014, MORA is in charge for establishing five major programs in conducting religious development. Two of them are: 1) improving the quality of religious life, 2) improving religious harmony.The implementation of this religious life arrangement is visible in a number of decrees of the Ministry of Religious Affairs as well as in some joint decrees with other Ministries. Among these are such as: the decree of the Ministry of Religious Affairs No.70 / 1978 on Guidelines for Religious Broadcasting, Joint decree of the Ministry of Religious Affairs and the Ministry of Domestic Affairs No.1 / 1979 on Religious Broadcasting and Foreign Aids. What is new now being the joint regulation of the Minister of Religious Affairs and the Minister of Domestic Affairs No.9 and 8 year 2006 on Guidelines for the Duty of the Regent in Maintaining Religious Harmony and in Empowering FKUB (the Forum of Religious Harmony)